2003
DOI: 10.1002/lsm.10192
|View full text |Cite
|
Sign up to set email alerts
|

Can patients treat themselves with a small novel light based hair removal system?

Abstract: With adequate training and instruction, patients may administer self-treatments for hair removal with this small light based unit in a safe and effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 7 publications
0
34
0
4
Order By: Relevance
“…Trelles et al [27] showed by skin histology that the use of a filterless flashlamp-based system delivering 7.5 J/cm 2 (SpaTouch) leads to partial degeneration of the HFs and coagulation changes in the adjacent tissue. Also clinically this device leads to relative strong treatment effects including side effects like edema, crusting and even blistering [12]. These strong effects are most probably the result of the ''Light and Heat Energy'' technology 3 by which also a substantial amount of heat energy is delivered to the skin.…”
Section: Low Fluence Photoepilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Trelles et al [27] showed by skin histology that the use of a filterless flashlamp-based system delivering 7.5 J/cm 2 (SpaTouch) leads to partial degeneration of the HFs and coagulation changes in the adjacent tissue. Also clinically this device leads to relative strong treatment effects including side effects like edema, crusting and even blistering [12]. These strong effects are most probably the result of the ''Light and Heat Energy'' technology 3 by which also a substantial amount of heat energy is delivered to the skin.…”
Section: Low Fluence Photoepilationmentioning
confidence: 99%
“…The reported types of immediate damage include severe damage to the hair shafts, the follicle inner root sheath (IRS) and outer root sheath (ORS), including thermal coagulation and vaporization injury [8][9][10][11][12][13]. It has also been shown that effective hair reduction can be obtained even though the hair shaft remains in place for several days before being shed [14].…”
Section: Introductionmentioning
confidence: 99%
“…These seven prospective studies were evaluated for efficacy and adverse effects and are summarized in Table 2. One study was categorized as a CT 7 and six as UCTs 8–13 . A total of 24 studies were excluded because they did not assess the efficacy of light‐based home use devices according to our a priori methodological criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Los aparatos que emplean la luz para tratamientos domiciliarios se conocen desde el año 2003 (1,2). Actualmente, Europa ha visto el lanzamiento en los comercios tradicionales y de venta por catalogo de varios sistemas de uso casero para depilación y para rejuvenecimiento de la piel.…”
Section: Introductionunclassified